Balancing costs and benefits in primates: ecological and palaeoanthropological views. (11th January 2021) - Garcia, Cécile; Bouret, Sébastien; Druelle, François; Prat, Sandrine
Abstract : Maintaining the balance between costs and benefits is challenging for species living in complex and dynamic socio-ecological environments, such as primates, but also crucial for shaping life history, reproductive and feeding strategies. Indeed, individuals must decide to invest time and energy to obtain food, services and partners, with little direct feedback on the success of their investments. Whereas decision-making relies heavily upon cognition in humans, the extent to which it also involves cognition in other species, based on their environmental constraints, has remained a challenging question. Building mental representations relating behaviours and their long-term outcome could be critical for other primates, but there are actually very little data relating cognition to real socio-ecological challenges in extant and extinct primates. Here, we review available data illustrating how specific cognitive processes enable(d) modern primates and extinct hominins to manage multiple resources (e.g. food, partners) and to organize their behaviour in space and time, both at the individual and at the group level. We particularly focus on how they overcome fluctuating and competing demands, and select courses of action corresponding to the best possible packages of potential costs and benefits in reproductive and foraging contexts. This article is part of the theme issue 'Existence and prevalence of economic behaviours among non-human primates'.